The role of psychological capital in flourishing among job seekers: Grit as a mediator - Wan Sulaiman, Wan Shahrazad; Shariff, Mohammad Izzat Akmal bin; Khairudin, Rozainee (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Psychological resources are crucial in enhancing individual potential, yet few studies have focused on positive psychological variables among job seekers. Therefore, the objective of this study is to examine the influence of psychological capital on flourishing, with grit as a mediator. A cross-sectional survey method was employed, with data collected using questionnaires involving 226 participants. Three instruments were included in the questionnaire: the Psychological Capital Questionnaire (PCQ), the Flourishing Scale, and the Short Grit Scale. The data were analyzed using bootstrapping mediation analysis via PROCESS software. The results show that all the psychological capital dimensions (hope, efficacy, resilience, and optimism) significantly influenced grit, with β ranging from .21 to .57 (p <.000), and also significantly influenced flourishing, with β ranging from .23 to .40 (p <.000). Grit also significantly mediated the psychological capital dimensions and flourishing. These findings indicate that psychological capital, grit and flourishing are important in developing individuals’ potential. It is hoped that they will be useful in designing employability training which incorporates positive psychology resources as intervention modules to assist graduates seeking job opportunities.